Drought stress modifies the community structure of root-associated microbes that improve Atractylodes lancea growth and medicinal compound accumulation - Wang, Hongyang; Wang, Yuefeng; Kang, Chuanzhi; Wang, Sheng; Zhang, Yan; Yang, Guang; Zhou, Li; Xiang, Zengxu; Huang, Luqi; Liu, Dahui; Guo, Lanping (Frontiers in Plant Science, 2022)
Atractylodes lancea is an important medicinal plant in traditional Chinese medicine, its rhizome is rich of volatile secondary metabolites with medicinal values and is largely demanded in modern markets. Currently, supply of high-yield, high-quality A. lancea is mainly achieved via cultivation. Certain soil microbes can benefit plant growth, secondary metabolism and induce resistance to environmental stresses. Hence, studies on the effects of soil microbe communities and isolates microorganisms on A. lancea is extremely meaningful for future application of microbes on cultivation. Here we investigated the effects of the inoculation with an entire soil microbial community on the growth, resistance to drought, and accumulation of major medicinal compounds (hinesol, β-eudesmol, atractylon and atractylodin) of A. lancea. We analyzed the interaction between A. lancea and the soil microbes at the phylum and genus levels under drought stress of different severities (inflicted by 0%, 10% and 25% PEG6000 treatments). Our results showed that inoculation with soil microbes promoted the growth, root biomass yield, medicinal compound accumulation, and rendered drought-resistant traits of A. lancea, including relatively high root:shoot ratio and high root water content under drought. Moreover, our results suggested drought stress was more powerful than the selectivity of A. lancea in shaping the root-associated microbial communities; also, the fungal communities had a stronger role than the bacterial communities in protecting A. lancea from drought. Specific microbial clades that might have a role in protecting A. lancea from drought stress were identified: at the genus level, the rhizospheric bacteria Bacillus, Dylla and Actinomadura, and rhizospheric fungi Chaetomium, Acrophialophora, Trichoderma and Thielava, the root endophytic bacteria Burkholderia-Caballeronia-Paraburkholderia, Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Dylla and Actinomadura, and the root endophytic fungus Fusarium were closely associated with A. lancea under drought stress. Additionally, we acquired several endophytic Paenibacillus, Paraburkholderia and Fusarium strains and verified they had differential promoting effects on the medicinal compound accumulation in A. lancea root. This study reports the interaction between A. lancea and soil microbe communities under drought stress, and provides insights for improving the outcomes in A. lancea farming via applying microbe inoculation.